Updates on the Management of Thyroid Cancer - Araque, Katherine A.; Gubbi, Sriram; Klubo-Gwiezdzinska, Joanna (Hormone and Metabolic Research, 2020)
The diagnostic modalities, stratification tools, and treatment options for patients with thyroid cancer have rapidly evolved since the development of the American Thyroid Association (ATA) guidelines in 2015. This review compiles newer concepts in diagnosis, stratification tools and treatment options for patients with differentiated thyroid cancer (DTC), medullary thyroid carcinoma (MTC) and anaplastic thyroid cancer (ATC). Newer developments apply precision medicine in thyroid cancer patients to avoid over-treatment in low risk disease and under-treatment in high risk disease. Among novel patient-tailored therapies are selective RET inhibitors that have shown efficacy in the treatment of MTC with limited systemic toxicity compared with non-specific tyrosine kinase inhibitors. The combination of BRAF and MEK inhibitors have revolutionized management of BRAF V600E mutant ATC. Several immunotherapeutic agents are being actively investigated in the treatment of all forms of thyroid cancer. In this review, we describe the recent advances in the diagnosis and management of DTC, MTC, and ATC, with an emphasis on novel treatment modalities.
Keywords: thyroid cancer; differentiated; medullary; anaplastic; updates